Pengaruh Kontaminasi Hasil Korosi Logam dari Alat Ortodontik Cekat terhadap Alergi pada Rongga Mulut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The aim of this orthodontic literature survey is to know how far the Influence of metal corrosion from the orthodontic fixed appliances toward the allergic in the oral cavity. The.conclusion of this survey are :1). The metal of fixed appliances that are used in the mouth should be had of high resistance corrosion. Stainless steel is suitable for it, besides that it is cheaper than other metal alloy, 2). Orthodontic treatment that uses stainless steel alloy from nickel chromium is better than nickel titanium toward the possibility of allergic incidences . 3). There is a relationship between personal history of metal allergic reaction and uses metal object on the skin with hypersensitivity of using nickel in the mouth. 4). Severe gingivitis, ulcers in oral mucous of the patients of orthodontic treatment needs to have more attention the possibility of hypersensitivity reaction to nickel or chromium toward the component of fixed appliances.